Ecohydrological processes and ecosystem services in the Anthropocene: a review - Sun, Ge; Hallema, Dennis; Asbjornsen, Heidi (Ecological processes, 2017)
The framework for ecosystem services has been increasingly used in integrated watershed ecosystem management practices that involve scientists, engineers, managers, and policy makers. The objective of this review is to explore the intimate connections between ecohydrological processes and water-related ecosystem services in human-dominated ecosystems in the Anthropocene. We synthesize current literature to illustrate the importance of understanding the ecohydrological processes for accurately quantifying ecosystem services under different environmental and socioeconomic settings and scales. Our synthesis focuses on managed ecosystems that are dominated by humans and explores how ecological processes affect the tradeoffs and synergies of multiple ecosystem services. We identify research gaps in studying ecological processes mainly including energy, carbon, water, and nutrient balances to better assess and quantify ecosystem services that are critical for sustaining natural resources for future generations. To better assess ecosystem services, future ecohydrological studies need to better account for the scaling effects of natural and anthropogenic stressors exerted on evapotranspiration and other water supply and demand processes. Future studies should focus on the bidirectional interactions between hydrological functions and services and human actions to solve real world problems such as water shortages, ecological degradation, and climate change adaptation.